Florida Flower Thrips (suggested common name) Frankliniella bispinosa Morgan (Insecta: Thysanoptera: Thripidae) - Steven P. Arthurs; Moh Leng Kok-Yokomi; Hugh Smith (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 5-page fact sheet that discusses the Florida flower thrips was written by Steven P. Arthurs, Moh Leng Kok-Yokomi, and Hugh Smith, and published by the UF Entomology and Nematology Department, November 2015.